Theoretical Treatment of Ultrafast Decay of Excited Vibronic States in the Improved Adiabatic Approximation (Communications in Computational Chemistry, 2022)
In the present paper, the non-radiative transition ${\rm S}_1→{\rm S}_0$ of pyrazine wasinvestigated by employing the improved Born-Oppenheimer adiabatic approximation,in which the conical intersection is shown to be avoided. Vibrational frequencies,normal coordinates, and non-adiabatic coupling matrix elements were obtained by ab initio quantum chemical methods. Calculated rate constants of internal conversion ${\rm S}_1→{\rm S}_0$ are $τ(υ=0)=61.7 $ ps and $τ(υ=1)=61.2$ ps in good agreement with the experimentalfindings.